(untitled) (Revista Brasileira Multidisciplinar, 2025)
There is a growing interest in advancing the development of biofuels, with biodiesel entering the Brazilian national market. The oxidative stability of biodiesel, or induction period (IP), is one of the important factors for determining the quality of this biofuel, thus allowing its commercialization and ensuring its validity during storage. Biodiesel is formed by methyl or ethyl esters with the presence of unsaturations from the raw material used in the synthesis, making it susceptible to the oxidation reaction. Natural extracts are replacing antioxidant additives of synthetic origin. This research aimed to evaluate the influence of adding lab lab leaves extract as a natural antioxidant additive on the oxidative stability of biodiesel and kinetic parameters. Samples containing extract showed higher induction periods and lower rate constants when compared to the control in the test at a temperature of 110°C. Since the leaves have low costs, lab lab extract with antioxidant properties has potential for commercial application to increase the oxidative stability of biodiesel.